THE EFFECT OF DEPOSITION TIME ON FILTRATION EFFICIENCY OF ELECTROSPUN NANOFIBRE WATER FILTERS - Nurfaizey, A.H.; Roslan, N.S.A.; Hafiz, M.I.M.; Rosli, M.A.M.; Saad, A.M.; Tucker, N. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
Growing concern over turbidity of river waters due to high presence of solid suspensions has encouraged the development of new type of efficient water filters. In this study, a new type of water filter was developed by incorporating electrospun nanofibres. The relationship between the amount of incorporated nanofibres in term of deposition time and filtration efficiency was studied. Nylon 6 solution at 20 wt.% concentration was electrospun onto standard glass fibre filters. A high voltage of 14 kV was supplied at the spinneret and electrospinning distance was set at 10 cm. Suspended solid retention test was conducted on the glass fibre filters using a vacuum filtration system based on BS EN 872 standard. The morphology of the filters was studied using scanning electron microscopy and ImageJ software. From the results, the suspended solid retention capability increased linearly with nanofibre deposition time. Due to small size of the nanofibres, the addition of nanofibre layer has increased the total porosity of the filter. Findings from this study could open up further understanding in new generation of water filters.